If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(-3x + -3) = 5x Reorder the terms: 6(-3 + -3x) = 5x (-3 * 6 + -3x * 6) = 5x (-18 + -18x) = 5x Solving -18 + -18x = 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. -18 + -18x + -5x = 5x + -5x Combine like terms: -18x + -5x = -23x -18 + -23x = 5x + -5x Combine like terms: 5x + -5x = 0 -18 + -23x = 0 Add '18' to each side of the equation. -18 + 18 + -23x = 0 + 18 Combine like terms: -18 + 18 = 0 0 + -23x = 0 + 18 -23x = 0 + 18 Combine like terms: 0 + 18 = 18 -23x = 18 Divide each side by '-23'. x = -0.7826086957 Simplifying x = -0.7826086957
| 7x+5x-54=72-6x | | 2c-58=7c-24 | | -15=5b+12-2b+b | | 3x+2+2x-1=6x-20 | | 35.8x+5.90=220.7 | | 17=6z-1 | | 36+(4x-9)=c(2x+1)+25 | | .666=3r | | 18x^2+18y^2-12x+9y+7=0 | | x^2-15x-15=-6x-5 | | -5+-16= | | 2b-8=0.4 | | (4x+7y)+(x-3y)= | | 5-2x=-5-x | | k+(4.21)=19.3 | | 13x+50=180 | | x^2-13x+28=-2x+4 | | -8=6b-14 | | 66.6=3r | | 3e=.75 | | x^2+13x+41=5 | | -(8y+5)-(-7y-7)=2 | | 2g-7g=-24 | | 6x+39=14x-66 | | -2(x-4)=12 | | 7x+3y=6x+5y | | -2(-2-4)=12 | | 6=4d-10 | | Y-4=7x(x-3) | | 5+5q=6+4q | | 6(2+-5)+5t=60-1 | | 11-j=2 |